Performing the Canadian "Mosaic": Juliette Gauthier, Florence Glenn, and the CPR Festivals of Quebec City - Sheedy, Erin (Université d'Ottawa / University of Ottawa, 2014)
The Quebec City festivals of 1927 and 1928 represent a unique instance of close collaboration between prominent figures in Canadian musical and cultural history, John Murray Gibbon and Marius Barbeau. Based on Anglocentric concerns for a unique Canadian identity and corresponding school of composition, the festivals served as points of contact between many artists and performers, including Juliette Gauthier and Florence Glenn. An analysis of specific performances at the CPR festivals and over the course of Glenn and Gauthier’s respective careers showcase how racialized attitudes towards Indigenous populations, and the static conceptualization of French-Canadian folk culture were navigated to perform “Canadian folksong.”
Keywords: Folk Music; Canada; Florence Glenn; Juliette Gauthier; Marius Barbeau; John Murray Gibbon; Representation; Authenticity; Canadian Pacific Railway; Festivals; Nationalism; Identity; Heritage; Tourism